The media and democracy - Keane, John, 1949- (Cambridge, MA : Polity in association with Basil Blackwell, 1991)
This book is a guide to rethinking the relationship between the media and democracy.
Keywords: Politics; Press; Mass media -- Political aspects; Press and politics; Freedom of the press